Phytopharmaceutical Potential of Clove Tea Bags as an Antihyperuricemic Agent in a Hyperuricemic Rat Model - Adrien Jems Akiles Unitly; Amos Killay; Maria Nindatu; Debby Dijola Moniharapon; Veince Benjamin Silahooy; Beatrix Belina Sikafir; Mechiavel Moniharapon; Theresia Natalia Seimahuira; Kezia Josawel Lesbatta; Eka Safitri Sillehu; La Eddy; Nia Doritha Laratmase (Pattimura University, 2026)
High protein dietary patterns, particularly those rich in animal protein containing high purine levels, may lead to hyperuricemia characterized by elevated blood uric acid levels. This study aimed to evaluate the phytopharmaceutical activity of clove tea bags on changes in blood uric acid levels in hyperuricemic Rattus norvegicus rats. The study employed a completely randomized design consisting of five treatment groups with three replications. The groups included a negative control without potassium bromate induction or clove tea administration, a positive control induced with 29 g potassium bromate to establish a hyperuricemia model, and three treatment groups induced with hyperuricemia followed by clove tea administration at doses of 0.234 g/head/day, 0.351 g/head/day, and 0.468 g/head/day for 14 days. Data were analyzed to determine differences in blood uric acid levels among groups. The results demonstrated that clove tea administration reduced blood uric acid levels, with the most effective dose being 0.234 g/head/day. These findings suggest that clove tea has potential as a natural therapeutic agent for managing hyperuricemia and contributes to the development of plant-based functional interventions.